Citrus Aurantium and caffeine complex versus placebo on biomarkers of metabolism: a double blind crossover design - Brian Kliszczewicz; Emily Bechke; Cassie Williamson; Zackery Green; Paul Bailey; John McLester; Cherilyn McLester (Taylor & Francis Group, 2019)
Backgrouond The purpose of this study was to examine resting the metabolic response to the ingestion of a complex containing Citrus Aurantium + Caffeine (CA + C) and if its consumption influences metabolic recovery following a high-intensity anaerobic exercise bout in habitual caffeine users. Methods Ten physically active males (25.1 ± 3.9 years; weight 78.71 ± 9.53 kg; height 177.2 ± 4.6 cm; body fat 15.5 ± 3.13%) participated in this study. This study was performed in a double-blind, randomized crossover fashion consisting of two exhaustive exercise protocols. On each visit the participants consumed either a CA + C (100 mg of CA and 100 mg of C) or placebo (dextrose) capsule. After consumption, participants were monitored throughout a 45-min ingestion period, then completed a repeated Wingate protocol, and were then monitored throughout a 45-min recovery period. Metabolic function was measured through blood glucose, plasma insulin, plasma triglycerides, and plasma catecholamines: epinephrine (E) and norepinephrine (NE). Biomarkers were taken at four different time points; Ingestion period: baseline (I1), post-ingestion period (I2); Recovery period: immediately post-exercise (R1), post-recovery period (R2). Results A repeated measures ANOVA revealed significant time-dependent increases in plasma E and NE at I2 only in the CA + C trial (p < 0.05), and a significant decrease in blood glucose at I2 in the PLA trial (p < 0.05); however, no meaningful changes in glucose was observed following CA + C ingestion. No changes in insulin or triglycerides were observed during the ingestion period. No trial-dependent differences were observed in the Recovery period. All biomarkers of metabolic recovery were equivalent when evaluating R1 v R2. Participants recovered in a similar time-dependent manner in all markers of metabolism following the PLA and CA + C trials. Conclusion The findings of this study suggested that normal recommended dosages of 100 mg CA + 100 mg C is sufficient to promote glucose sparing at rest, with modest increases in SNS activity; however, the individual role of CA or C in this response cannot be determined.